Translating pumping test data into groundwater model parameters: a workflow to reveal aquifer heterogeneities and implications in regional model parameterization - Manewell, Neil; Doherty, John; Hayes, Phil (Frontiers in Water, 2024)
Groundwater modellers frequently grapple with the challenge of integrating aquifer test interpretations into parameters used by a regional model. This challenge is multifaceted as it encompasses issues of upscaling, data assimilation and the assignment of prior probability distributions to regional model parameters. This study introduces a new framework that accounts for the significant differences in scale between aquifer tests and regional models. It also accounts for loss of original drawdown datasets on which historical pumping test interpretations were based, as well as the heterogeneous nature of geological media in which aquifer testing takes place. First, the aquifer test is reproduced on a fine numerical grid that can provide stochastic representation of arbitrary hydraulic property complexity. Data space inversion is then employed to populate pertinent cells of a regional model grid with upscaled, aquifer-test constrained realisations of its parameters. These are used to condition the parameters of other regional model cells. An example is presented. Outcomes of this example suggest that assimilation of historical pumping test interpretations into a regional model can influence the posterior mean of model predictions. On the other hand, the uncertainties of model predictions may not be reduced by much.